ZmABA2, an interacting protein of ZmMPK5, is involved in abscisic acid biosynthesis and functions. Issue 2 (19th June 2015) - Ma, Fangfang; Ni, Lan; Liu, Libo; Li, Xi; Zhang, Huan; Zhang, Aying; Tan, Mingpu; Jiang, Mingyi
Summary: In maize ( Zea mays ), the mitogen‐activated protein kinase ZmMPK5 has been shown to be involved in abscisic acid (ABA)‐induced antioxidant defence and to enhance the tolerance of plants to drought, salt stress and oxidative stress. However, the underlying molecular mechanisms are poorly understood. Here, using ZmMPK5 as bait in yeast two‐hybrid screening, a protein interacting with ZmMPK5 named ZmABA2, which belongs to a member of the short‐chain dehydrogenase/reductase family, was identified. Pull‐down assay and bimolecular fluorescence complementation analysis and co‐immunoprecipitation test confirmed that ZmMPK5 interacts with ZmABA2 in vitro and in vivo . Phosphorylation of Ser173 in ZmABA2 by ZmMPK5 was shown to increase the activity of ZmABA2 and the protein stability. Various abiotic stimuli induced the expression of ZmABA2 in leaves of maize plants. Pharmacological, biochemical and molecular biology and genetic analyses showed that both ZmMPK5 and ZmABA2 coordinately regulate the content of ABA. Overexpression of ZmABA2 in tobacco plants was found to elevate the content of ABA, regulate seed germination and root growth under drought and salt stress and enhance the tolerance of tobacco plants to drought and salt stress. These results suggest that ZmABA2 is a direct target of ZmMPK5 and is involved in ABA biosynthesis and functions.